The perception of Indonesia General Practitioners in Medan toward the roles of family physician (Dokter Keluarga) a comparative study between with and without continuing medical education on family medicine - Fujiati, Isti Illmiati
Background: To anticipate the changes in the medical services to societal and global demands, the primary health care that used to be attended by general practitioners are now being handled by the family doctors The Department of Health of Indonesia, Indonesian Doctors Association, Indonesian College of Family Physicians and the School of Medicine, developed modules of education of family physicians. Medan is one of the Chapters of the Indonesian College of Family Physician that have produced two batches of the continuing medical education (CME) program on family medicine for modules A and B. Objectives: This study aims to determine whether a continuing medical education (CME) on family medicine would enhance general practitioners' perception of family physician, nd to identify whether the participants' characteristics may affect their perception of the family physician. Methodology: This is an analytic cross sectional study. The study was based on a questionnaire as a research tool. The questionnaire was given to 36 general practitioners who attended the CME on family medicine and 126 general practitioners who didi not attend CME. The study was conducted on April 30,2002 until May 31, 2002 in Meda, Indonesia. Results: In this study, the general practitioners (GPs) were asked to rank their perception towards the roles of the family physycian in six domains of concern. The result showed CPs participants were generally in fvor of the roles of the familu physician, with mean scores indicating a positive perception on the roles in 32 of the 34 statements in the questionnaire. However, the CME participants were significantly different, that they are more positive than the non-CME participants to 15 statements of 32 positive statements. The result showed the characteristics of the participants were influenced by their perception toward the roles. The CME has an effect on the more positive perception of the participants toward every domain of the roles. Femarles have lower positive perception than male. based on the age, younger general practitioners (40 years old and below) are more likely to have positive perception to the roles than participants 41 years old and above. Based on the civil status, married participants have more positive perception than singe/widow/widower participants. Tribes of cultures/ethnic also affect their perception. The Javanese are more likely to have positive perception in almost every role of the family physician than the Bataks. In type of practice, group practice has lower positive perception in almost every domain of the roles. The place of work seems to have great effect on their perception toward the roles of family physicians. Conclusion: The study results showed that the continuing medical education (CME) enhanced the general practitioners perception toward the roles of family physicians. The positive perception of majority of the participants supports it to continue the CME on family medicine in Medan, Indonesia to anticipate the changes in medical services in primary care.
Theses--(Master of Science in Clinical Medicine-Family Medicine) UPCM
Keywords: Medical education